Cause of flow distributor on flow uniformity in open waterway stream passage velocity comparisons. Issue 5 (15th April 2020) - Senthilkumar, G.; Anderson, A.; Lakshmi Sankar, S.
Abstract : In an open waterway flow passage, the inclusion of flow distributor paves a way to understand the idea of flow uniformity of the water along the upstream side and prevents non-uniform flow of water besides the passage length as a function of flow rate. The interesting idea in the flow distributor is its length and porosity. The essential conditions that should be satisfied are: there should not be any turbulence and there should be a possibility of achieving uniform circumferential flow in the flow passage. The other critical issue is the accurate measurement of low velocity of water. In this paper, a propeller-turbine-type anemometer is specially designed, fabricated and calibrated to measure the local velocity of water in the range of 0.001–0.01 m/s. This paper signifies how the flow uniformity is achieved by varying the size and porosity of the flow distributor.